A tale of two societies: implications of conflicting Rh-immunoglobulin guidelines - Cara Heuser, MD, MS; Rachel Flink-Bochacki, MD, MPH; Jeffrey Sperling, MD; Katharine Simmons, MD, MPH; Kirsten Salmeen, MD (Elsevier, 2024)
National guidance conflicts regarding the use of RhD immune globulin administration <12w. Recent Society for Maternal Fetal Medicine (SMFM) guidelines suggest liberal use of this product while other guidelines, including Society of Family Planning and the World Health Organization, propose a more conservative approach. Medicine is not practiced in a vacuum, and potential harms must include not only individual but communal and public health effects. We aim to critically examine the practical implications of the new SMFM guidelines with a focus on equity and access.